Budaya Hidup Sehat di Era New Normal Bagi Guru SMPN 1 Tegalampel Bondowoso - Bayu Akbar Harmono Wahyono; Luqmanul Hakim; Angga Indra Kusuma; Ismawandi Bripandika; Eka Kurnia Darisman; Yandika Fefrian. R; Gatot Margisal Utomo (Kanigara, 2022)
In order to prepare for offline learning, SMPN 1 Tegalampel Bondowoso needs many references on how to maintain a healthy lifestyle in the pandemic era to avoid covid-19. Starting from knowledge about immunity. Therefore, it is necessary to hold counseling on maintaining a healthy lifestyle at SMPN 1 Tegalampel Bondowoso. The implementation of Community Service Program activities by the Physical Education Lecturer Team at PGRI Adi Buana University Surabaya went smoothly. The teachers of SMPN 1 Tegalampel Bondowoso were very enthusiastic about participating in every scheduled activity. In order to prepare for offline learning, SMPN 1 Tegalampel Bondowoso needs many references on how to maintain a healthy lifestyle through exercise in the pandemic era to avoid covid-19. Starting from knowledge about maintaining a healthy lifestyle, increasing immunity by improving nutrition, increasing immunity by exercising and other knowledge that can provide benefits.